Tax Implications on Financial Instruments Resulting From IFRS 9 Adoption in Indonesia - Prianto Budi Saptono; Ismail Khozen (Jurnal Reviu Akuntansi dan Keuangan, 2021)
This study aims to analyze the tax implications of financial instruments after International Financial Reporting Standards (IFRS) 9 adoption in Indonesia into Statement of Financial Accounting Standard 71 (PSAK 71). To gain an in-depth understanding regarding the implementation of PSAK 71, we conducted semi-structured in-depth interviews with policymakers, PSAK standard setters, academicians, tax consultants, and taxpayers. We also used case studies related to the convergence of IFRS 9 to identify the tax implications of implementing the new standard. The results show that the entities applying PSAK 71 generally measure and recognize financial assets or financial liabilities at fair value. Besides, they use amortized costs in specific conditions. However, current tax regulations relevant to financial instruments still refer to the acquisition cost following Article 10 of the Income Tax Law. Accordingly, the gains or losses in respect of financial instruments are not recognizable for tax purposes. Although fiscal correction has proven to be a panacea for bridging the gap between taxation and accounting standards, policymakers urgently need to revise the outdated regulations to provide taxpayers with legal certainty and ease of administration. The significant contribution of this study is the attempt to link the accounting and taxation aspect of financial instruments with the setting of Indonesia.